Relationship between growing pig’s housing conditions, behaviours, lesions and health issues under Italian farming system - Francesco Palumbo; Diana Luise; Sara Virdis; Federico Correa; Patrizia Bassi; Paolo Trevisi (Italian Journal of Animal Science)
Low space availability, high temperatures and a barren environment may contribute to the occurrence of abnormal behaviours and lesions in intensive pig farming. The present study evaluated the housing conditions (HCs), that influence behavioural measures (BMs), and lesion and health measures (LHMs) in growing pigs reared in an Italian farming system. Data collection was carried out on two groups of pigs in each farm (Farm A and Farm B), tail docked (DT) and tail undocked (UT). The HCs measured were dry and wet bulb temperature, light, humidity, air quality, average body weight, pen level of cleanliness, space, and feeder front allowance. Light intensity was negatively associated with positive behaviour (coefficient: −0.01; p < 0.001), while the length of the feeder front was positively associated with the proportion of pigs exploring the pen (coefficient: 65.18; p = 0.04). Tail lesion score index (LSI) increased with an increased frequency of negative behaviour (coefficient: 8.05; p < 0.01), increased light intensity (coefficient: 0.29; p < 0.001) and increased proportion of CO2 (coefficient: 498.31; p < 0.001), while it decreased with the average body weight of the pen (coefficient: −4.04; p < 0.001) and the space allowance (coefficient: −198.93; p < 0.001). Finally, UT pigs showed a greater (p < 0.001) tail LSI than DT pigs (126.8 ± 5.71 and 78.5 ± 9.11, respectively for UT and DT pigs). The present study improved the understanding of the effects of HCs, including tail docking, on welfare parameters of growing pigs.HIGHLIGHTS Housing and management conditions might play a prominent role on pig health and welfare parameters during growing period. Social and exploring attitude behaviours affects both ears and tail lesions. Regardless of tail docking, tail injuries were positively associated with negative behaviour, light intensity, and CO2, while they were negatively associated with the average body weight of the pen and the space allowance.